African yearbook of international law Vol 8, 2000 = Annuaire africaine de droit international Vol 8, 2000 (Leiden Brill/Nijhofff, 2001)
Thirty years on : a legal review of the 1969 OAU Refugee Convention, by George Okoth-Obbo. The admission and expulsion of refugees with special reference to Africa by Georges Abi-Saab. Africa's refugees : patterns, problems and policy challenges, by Jeff Crisp. The African refugee crisis : contemporary challenges to the protection of refugees and displaced persons in Africa by Robin Ramcharan. African refugees in Europe : the right to seek asylum and the authority of international refugee law : the case of the United Kingdom, by Monica Feria Tinta.
Series of articles.
Includes bibliographical references.
Keywords: UNHCR; Refugees; Displaced persons; Immigration policy; Right of asylum; Refugee protection; International law; Refugee law; Case studies; Africa; Europe; United kingdom